Genetic resources of lotus (Nelumbo) and their improvement - Ping Zhou; Qijiang Jin; Ping Qian; Yanjie Wang; Xiaowen Wang; Huiyan Jiang; Dongrui Yao; Xiaojing Liu; Fengjun Liu; Jun Li; Yingchun Xu (Ornamental Plant Research, 2022)
Lotus (Nelumbo) is one of the top ten flowers in China, which has high ornamental, edible and medicinal value. Lotus has a been cultivated for thousands of years. Through discovery and cultivation, more than 4,000 cultivars have been recorded. However, the information related to lotus breeding is quite scattered, and the related genetic rules and trait formation mechanisms are still poorly understood, which has caused a greater impact on lotus genetic breeding. This article systematically introduces lotus germplasm resources, including wild species and cultivated species, summarizes lotus breeding methods and breeding directions, and focuses on the latest progress in the isolation and functional identification of structural and regulatory genes related to important horticultural traits. Prospects for the protection and utilization of lotus resources, breeding and industrialization are reported.